MODERASI INFLASI PADA PENGARUH DIVIDEND PAYOUT RATIO (DPR) DAN RETURN ON EQUITY (ROE) TERHADAP RETURN SAHAM - Ni Nyoman Sri Rahayu Trisna Dewi (Badung: LPPM Universitas Triatma Mulya, 2021)
Investors definitely expect a high return on the investment made. To obtain a high return, investors need to analyze the investment they are making. The analysis carried out can be a fundamental analysis that assesses the company's financial capacity by looking at financial reports. Fundamental analysis can be done by assessing the DPR and ROE produced by the company. Apart from fundamental analysis, investors also need to pay attention to macro factors such as inflation that can affect their investment. This study aims to determine the effect of DPR and ROE partially on stock returns and to determine the moderation of inflation in each of the effects of DPR and ROE on stock returns. The object of this research are companies listed on the LQ45 index for the 2018-2019 period. The sample method used was purposive sampling in order to obtain a sample size of 40 samples. The data analysis technique used moderate regression analysis. The results showed that the DPR did not have a significant effect on stock returns while ROE had a positive and significant effect on stock returns. The results also show that inflation does not moderate the respective effects of DPR and ROE on stock returns.